The Effect of Customer Engagement on Customer Loyalty Through Customer Satisfaction at Shopee - Hilda Fauziyah; Iskandar Iskandar; Wachjuni Wachjuni (Indonesian Journal Of Business And Economics, 2023)
This study aims to determine whether Customer Satisfaction (Z) completely mediates or partially mediates the relationship between Customer Engagement (X) and Customer Loyalty (Y). The research problem addressed the lack of loyalty towards the Shopee marketplace, as preliminary survey results indicated obstacles such as difficulties in returning products and funds, inability to choose preferred shipping services, and negative experiences that deterred revisiting the Shopee website. The sample for this study consisted of students in Kuningan Regency. The author employed the survey method and distributed questionnaires through Google Forms to 140 respondents. Data collection was conducted using questionnaires, and the measurement used an interval scale. The data obtained were analyzed used the mediation regression analysis method, which involved testing simple regression analysis and multiple regression analysis to determine whether Customer Satisfaction (Z) completely mediates or partially mediates the relationship between Customer Engagement (X) and Customer Loyalty (Y). The analysis was performed used Statistical Program for Social Sciences (SPSS) version 23. The testing results of the proposed hypotheses led to the conclusion that (1) Customer Engagement has a positive and significant influence on Customer Loyalty. (2) Customer Satisfaction (Z) completely mediates the relationship between Customer Engagement (X) and Customer Loyalty (Y).